2010
DOI: 10.1074/jbc.m109.076679
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Dissociation Constants for Ca2+ and Calmodulin from the Plasma Membrane Ca2+ Pump by a Lipid Probe That Senses Membrane Domain Changes

Abstract: The purpose of this work was to obtain information about conformational changes of the plasma membrane Ca 2؉ -pump (PMCA) in the membrane region upon interaction with Ca 2؉ , calmodulin (CaM) and acidic phospholipids. To this end, we have quantified labeling of PMCA with the photoactivatable phosphatidylcholine analog [125 I]TID-PC/16, measuring the shift of conformation E 2 to the auto-inhibited conformation E 1 I and to the activated E 1 A state, titrating the effect of Ca 2؉ under different conditions. Usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…This effect is analogous to the behavior observed for other activators of the pump such as CaM and phosphatidic acid (72,73).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…This effect is analogous to the behavior observed for other activators of the pump such as CaM and phosphatidic acid (72,73).…”
Section: Discussionmentioning
confidence: 51%
“…We have previously reported that treatments that lead to an activation of PMCA are related to a decrease in the accessible area of the membrane domain of the pump to the surrounding lipids, strongly suggesting the involvement of a conformational change in the transmembrane segments (49,72,73).…”
Section: Effect Of Actin On the Conformational State Of Pmcamentioning
confidence: 99%
“…Using the same experimental approach, we were also able to measure equilibrium constants for different ligands through the change of transmembrane conformations in PMCA (22). In order to obtain a complete understanding of the physical processes that involve ATP hydrolysis and Ca 2ϩ transport, it is necessary to know more about the structure of the enzyme.…”
Section: I]iodo-4-(trifluoromethyl-3h-diazirin-3-yl)benzyl]oxy]carbonmentioning
confidence: 99%
“…Labeling-A photolabeling assay was carried out as described by Mangialavori et al (21,22). A dried film of the photoactivatable reagent was suspended in PC/C 12 E 10 mixed micelles containing 10 g/ml of the membrane protein.…”
Section: Measurement Of Ca 2ϩmentioning
confidence: 99%
“…The plasma membrane calcium ATPase (PMCA) has since been classified as a member of the P-type transport ATPase family, due to the covalent intermediate state that is formed upon phosphorylation of a highly conserved aspartate residue during its catalytic cycle (285). The pumps are high affinity (0.2-0.5 M under optimal conditions) Ca 2ϩ extruders, binding a single intracellular Ca 2ϩ ion which is then deposited to the extracellular space following conformational changes which first allow transport of the ion through the plasma membrane and finally dissociation from the pump through lowering its Ca 2ϩ affinity (44,225). This means that compared with the related ATPase of the sarco(endo)plasmic reticulum (SERCA), the PMCA has a lower capacity for Ca 2ϩ clearance, removing only one Ca 2ϩ ion per ATP molecule hydrolyzed as opposed to two (143).…”
Section: Introductionmentioning
confidence: 99%